2001
DOI: 10.1093/ps/80.9.1323
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Environmental Origin Salmonellas in Specific Pathogen-Free Chicks

Abstract: Two hundred sixty 1-d-old specific pathogen-free (SPF), Single Comb White Leghorn chicks were used in this study to determine pathology caused by Salmonella enteritidis (SE) isolated from a poultry environment. The chicks were subdivided into 10 equal groups of 26 chicks each. Eight groups of chicks were inoculated individually with 0.5 mL of brain heart infusion broth culture containing 1 x 10(6) cfu of SE phage type (PT) -8 (1, 2, 3), SE PT5 A (1, 2), or SE PT4 (Ch-env-CA, chicken-CA, and human) by crop gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
4
14
1
2
Order By: Relevance
“…Between the evaluated lesions, aerossaculitis, peritonitis and onfalitis were the most common occurrences in both studied serotypes. These findings are similar to the ones described by many researches after experimental infection with S. Enteritidis (Desmidt et al, 1997;Dhillon et al, 1999;Alisantosa et al, 2000;Dhillon et al, 2001;Akthar et al, 2011;Akthar et al, 2013) and S. Typhimurium in Specific Pathogens Free (SPF) birds between one and twenty-eight days.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Between the evaluated lesions, aerossaculitis, peritonitis and onfalitis were the most common occurrences in both studied serotypes. These findings are similar to the ones described by many researches after experimental infection with S. Enteritidis (Desmidt et al, 1997;Dhillon et al, 1999;Alisantosa et al, 2000;Dhillon et al, 2001;Akthar et al, 2011;Akthar et al, 2013) and S. Typhimurium in Specific Pathogens Free (SPF) birds between one and twenty-eight days.…”
Section: Resultssupporting
confidence: 91%
“…Similarly Dhillon et al (2001) describes that pericarditis was not common in birds that were found dead after the inoculation with different fagotypes of S. Enteritidis. Nevertheless, this finding differs from the ones observed by Roy and contributors (2001) who describe the presence of fibrinous exudate in the pericardium as one of the main macroscopic lesions observed in SPF chicks after oral inoculation of 10 7 CFU of S. Typhimurium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hong'ombe et al (1999) identified S. enteritidis in broiler carcasses ready for market in several different situations. Many authors identified poultry products as sources of infection of Salmonella that causes enteritis in humans (Dhillon et al, 2001). Approximately 10% of salmonellosis cases are caused by poultry meat, and in the United States, there are between 15 and 20 cases of salmonellosis for each 100,000 people (Bryan & Doyle, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the challenge dose (1 × 10 5 CFU) administered to the chicks was selected to minimize the risk of any clinical signs and thus reduce the chance of any adverse consequences for the birds. A higher dose might have led to a more extensive tissue invasion, but could have caused clinical disease (Barrow et al, 1987;Dhillon et al, 2001). Strain F (4,5, and strain G (SE) colonized more effectively in the chicks (the number of positive tissues recovered was higher and there were positive samples after direct plating, suggesting that a higher number of salmonellas was present in the tissues).…”
Section: Discussionmentioning
confidence: 99%